Pemanfaatan Ekstrak Daun Erpa (Aerva sanguinolenta) untuk Label Cerdas Indikator Warna - Endang Warsiki; Rini Nofrida; Indah Yuliasih (Institut Pertanian Bogor, 2013)
The color of natural dyes, as anthocyanins, is very easily changing as he temperature changes. The color change can be used as a color indicator to provide information about product deterioration due to its sensitivity toward temperature and light. This indicator is called smart label of color indicator. This film label can be made of chitosan and polyvinyl alcohol and extract of erpa (Aerva sanguinolenta) leaves. The extraction was done under various leaf:water ratios. The filming was done in 2 methods, i.e. (i) by mixing the extract into film solution and drying the film at 50 °C; and (ii) by brushing the extract on the film surface. The leaf extract had a pH of 5.09 and the total yield of 116.65 mg anthocyanin/100 g leaves. Filming of color indicator in mixing method and dried at 50 °C resulted a colorless film. Brushing method was the best method to produce smart label with quite stable property and 1 mL extract could be applied evenly per 40 cm2 film area. Thus, this film can be utilized as smart label with color indicator to detect the deterioration in temperature-sensitive products.